Explaining Reallocation's Apparent Negative Contribution to Growth - Mitsukuni Nishida; Amil Petrin; Sašo Polanec (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2011)
We explain a puzzle from two recent meta-analyses that cover 25 countries and claim to show that inputs systematically move from higher- value to lower-value activities despite strong aggregate labor productivity growth (ALP). These papers use variants of the Baily, Hulten and Campbell ( 1992) decomposition of ALP to show that the reallocation covariance tfirm is negative in all but two countries and the reallocation between tfirm is negative in nine countries and weakly positive in most others. We decompose ALP using three micro-level data sets from Chile, Colombia and Slovenia and show the same puzzle holds. We show that the ALP between tfirm can be decomposed into a tfirm related to reallocation and a tfirm related to a change in the total number of firms, the latter of which often works to reduce the total between tfirm in our data. We also show these ALP patterns can arise because of heterogeneity in labor and capital, unobserved output prices or capacity utilization, but controlling for them only marginally helps to explain away the ALP reallocation puzzles in our micro-level data sets. We show that there is no puzzle when one decompose aggregate productivity growth in tfirms of National Accounts, as inputs in the aggregate move from low to high value activities in 36 of our 39 country-year observations. We conclude that there is a fundamental difference in reallocation measured by the ALP decomposition and that measured by the decomposition of National Accounts growth.
Keywords: 330